POLARIZATION OF ISLAMIC EDUCATION DURING THE UMAYYAH DAILY - Fahruddin, Zuhri (LTN NU Sulawesi Tengah, 2023)
Abstract Islamic education during the Umayyad Daulah era was essentially closely related to Islamic history. The polarization of Islamic education during the Umayyad period was always in line with the polarization of Islamic history itself. Therefore, this paper attempts to explain globally about polarization institution Islamic education during the Umayyad period through three problem formulations, namely: educational patterns during the Umayyah period; educational figures at that time, and the form of educational institutions at that time using a historical approach. The results of these three formulations show that the education pattern at this time is using a concentration system . Some of the famous ulama figures who represented Islamic cities at that time included: Abdullah bin Umar in Makah, Abdullah bin Mas'ud in Kufah, Abdullah bin Abbas in Makah, and Abdullah bin 'Amr bin 'Ash in Egypt. Madrasahs or educational institutions that were built at that time were Madrasah Makah, Madrasah Medina, Madrasah Bashrah, Madrasah Kufah, Madrasah Damascus (Damascus), and Madrasah Fustat in Egypt.